Genomics of Acute Myeloid Leukemia: The Next Generation - Riva, Laura; Luzi, Lucilla; Pelicci, Pier Giuseppe (Frontiers in Oncology, 2012)
Acute myeloid leukemia (AML) is, as other types of cancer, a genetic disorder of somatic cells. The detection of somatic molecular abnormalities that may cause and maintain AML is crucial for stratifying patients. The development of mutation-specific therapeutic interventions will hopefully increase cure rates and improve patients’ quality of life. This mini-review illustrates how next generation sequencing (NGS) technologies are changing the study of cancer genomics of adult AML patients.